Problem Solving Ability with Readiness to Enter Elementary School - Muhammad Nur Priyo Sudarmo; Lely Ika Mariyati (Psikologia : Jurnal Psikologi, 2017)
This study aims to explore the correlation between the readiness of students to enter elementary school with problem solving ability, as well as to describe the problem solving ability and the school readiness of students. The respondents involved in this study were 87 kindergarten students (TK-B). Sample determination was done by using saturated sampling technique. Data collection was done by administering two instruments, namely NST and WPPSI. NST is used to measure students 'readiness and WPPSI is used to measure students' problem solving ability. Data analyzed using Product-Moment correlation with correlation coefficient value (rxy) of 0.432 and significance level (p) of 0.000. The results showed that the problem solving ability has a significant relationship with the readiness of students in kindergarten level.